Heterometal nanoparticles from Ru-based molecular clusters covalently anchored onto functionalized carbon nanotubes and nanofibers - Vidick, Deborah; Ke, Xiaoxing; Devillers, Michel; Poleunis, Claude; Delcorte, Arnaud; Moggi, Pietro; Van Tendeloo, Gustaaf; Hermans, Sophie (Beilstein Journal of Nanotechnology, 2015)
Heterometal clusters containing Ru and Au, Co and/or Pt are anchored onto carbon nanotubes and nanofibers functionalized with chelating phosphine groups. The cluster anchoring yield is related to the amount of phosphine groups available on the nanocarbon surface. The ligands of the anchored molecular species are then removed by gentle thermal treatment in order to form nanoparticles. In the case of Au-containing clusters, removal of gold atoms from the clusters and agglomeration leads to a bimodal distribution of nanoparticles at the nanocarbon surface. In the case of Ru–Pt species, anchoring occurs without reorganization through a ligand exchange mechanism. After thermal treatment, ultrasmall (1–3 nm) bimetal Ru–Pt nanoparticles are formed on the surface of the nanocarbons. Characterization by high resolution transmission electron microscopy (HRTEM) and high angle annular dark field scanning transmission electron microscopy (HAADF-STEM) confirms their bimetal nature on the nanoscale. The obtained bimetal nanoparticles supported on nanocarbon were tested as catalysts in ammonia synthesis and are shown to be active at low temperature and atmospheric pressure with very low Ru loading.
Keywords: ammonia synthesis; cluster; nanofibers; nanoparticles; nanotubes

(untitled) - Serp, P.; Corrias, M.; Kalck, P. (Appl. Catal., A, 2003)

(untitled) - Wildgoose, G. G.; Banks, C. E.; Compton, R. G. (Small, 2006)

(untitled) - Capek, I. (Adv. Colloid Interface Sci., 2009)

(untitled) - Wu, B.; Kuang, Y.; Zhang, X.; Chen, J. (Nano Today, 2011)

(untitled) - Lee, K.; Zhang, J.; Wang, H.; Wilkinson, D. P. (J. Appl. Electrochem., 2006)

(untitled) - Liu, H.; Song, C.; Zhang, L.; Zhang, J.; Wang, H.; Wilkinson, D. P. (J. Power Sources, 2006)

(untitled) - Maiyalagan, T. (Int. J. Hydrogen Energy, 2009)

(untitled) - Carmo, M.; Paganin, V. A.; Rosolen, J. M.; Gonzalez, E. R. (J. Power Sources, 2005)

(untitled) - Bambagioni, V.; Bianchini, C.; Marchionni, A.; Filippi, J.; Vizza, F.; Teddy, J.; Serp, P.; Zhiani, M. (J. Power Sources, 2009)

(untitled) - Prabhuram, J.; Zhao, T. S.; Liang, Z. X.; Chen, R. (Electrochim. Acta, 2007)

(untitled) - He, Z.; Chen, J.; Liu, D.; Zhou, H.; Kuang, Y. (Diamond Relat. Mater., 2004)

(untitled) - Tsai, M.-C.; Yeh, T.-K.; Tsai, C.-H. (Electrochem. Commun., 2006)

(untitled) - Jeng, K.-T.; Chien, C.-C.; Hsu, N.-Y.; Yen, S.-C.; Chiou, S.-D.; Lin, S.-H.; Huang, W.-M. (J. Power Sources, 2006)

(untitled) - Liu, Z.; Ling, X. Y.; Guo, B.; Hong, L.; Lee, J. Y. (J. Power Sources, 2007)

(untitled) - Ren, L.; Xing, Y. (Electrochim. Acta, 2008)

(untitled) - Hernández-Fernández, P.; Nuño, R.; Fatás, E.; Fierro, J. L. G.; Ocón, P. (Int. J. Hydrogen Energy, 2011)

(untitled) - Yao, Y.-l.; Ding, Y.; Ye, L.-S.; Xia, X.-H. (Carbon, 2006)

(untitled) - Li, L.; Xing, Y. (J. Phys. Chem. C, 2007)

(untitled) - Li, J.; Liang, Y.; Liao, Q.; Zhu, X.; Tian, X. (Electrochim. Acta, 2009)

(untitled) - Li, W.; Wang, X.; Chen, Z.; Waje, M.; Yan, Y. (J. Phys. Chem. B, 2006)

(untitled) - Vu, H.; Gonçalves, F.; Philippe, R.; Lamouroux, E.; Corrias, M.; Kihn, Y.; Plee, D.; Kalck, P.; Serp, P. (J. Catal., 2006)

(untitled) - Teddy, J.; Falqui, A.; Corrias, A.; Carta, D.; Lecante, P.; Gerber, I.; Serp, P. (J. Catal., 2011)

(untitled) - An, G.; Yu, P.; Mao, L.; Sun, Z.; Liu, Z.; Miao, S.; Miao, Z.; Ding, K. (Carbon, 2007)

(untitled) - Yen, C. H.; Shimizu, K.; Lin, Y.-Y.; Bailey, F.; Cheng, I. F.; Wai, C. M. (Energy Fuels, 2007)

(untitled) - Xu, M.-W.; Su, Z.; Weng, Z.-W.; Wang, Z.-C.; Dong, B. (Mater. Chem. Phys., 2010)

(untitled) - Yang, C.; Hu, X.; Wang, D.; Dai, C.; Zhang, L.; Jin, H.; Agathopoulos, S. (J. Power Sources, 2006)

(untitled) - Jiang, Z.; Jiang, Z.-j. (Electrochim. Acta, 2011)

(untitled) - Xiao, F.; Zhao, F.; Mei, D.; Mo, Z.; Zeng, B. (Biosens. Bioelectron., 2009)

(untitled) - Xiong, L.; Manthiram, A. (Solid State Ionics, 2005)

Inorg. Synth. - Nicholls, J. N.; Vargas, M. D.; Hriljac, J.; Sailor, M. (Carbido-Carbonyl Ruthenium Cluster Complexes, 1989)

(untitled) - Hermans, S.; Khimyak, T.; Johnson, B. F. G. (J. Chem. Soc., Dalton Trans., 2001)

(untitled) - Bruce, M. I.; Horn, E.; Humphrey, P. A.; Tiekink, E. R. T. (J. Organomet. Chem., 1996)

(untitled) - Johnson, B. F. G.; Lewis, J.; Nelson, W. J. H.; Nicholls, J. N.; Puga, J.; Raithby, P. R.; Rosales, M. J.; Schröder, M.; Vargas, M. D. (J. Chem. Soc., Dalton Trans., 1983)

(untitled) - Cowie, A. G.; Johnson, B. F. G.; Lewis, J.; Raithby, P. R. (J. Chem. Soc., Chem. Commun., 1984)

(untitled) - Khimyak, T.; Johnson, B. F. G.; Hermans, S.; Bond, A. D. (Dalton Trans., 2003)

(untitled) - Steinhardt, P. C.; Gladfelter, W. L.; Harley, A. D.; Fox, J. R.; Geoffroy, G. L. (Inorg. Chem., 1980)

(untitled) - Hermans, S.; Khimyak, T.; Feeder, N.; Teat, S. J.; Johnson, B. F. G. (Dalton Trans., 2003)

(untitled) - Vidick, D.; Herlitschke, M.; Poleunis, C.; Delcorte, A.; Hermann, R. P.; Devillers, M.; Hermans, S. (J. Mater. Chem. A, 2013)

(untitled) - Hogarth, G.; Kabir, S. E.; Nordlander, E. (Dalton Trans., 2010)

(untitled) - Femoni, C.; Iapalucci, M. C.; Kaswalder, F.; Longoni, G.; Zacchini, S. (Coord. Chem. Rev., 2006)

Metal Clusters in Chemistry - Braustein, P.; Oro, L. A.; Raithby, P. R. (Wiley-VCH, 1999)

Encyclopedia of Catalysis - Horvath, I. T. (John Wiley & Sons, 2003)

(untitled) - Liang, C.; Wei, Z.; Xin, Q.; Li, C. (Appl. Catal., A, 2001)

(untitled) - Hinnemann, B.; Nørskov, J. K. (Top. Catal., 2006)

U. S. Patent - Foster, A. I.; James, P. G.; McCarroll, J. J.; Tennison, S. R. (Process for the synthesis of ammonia using catalysts supported on graphite containing carbon, 1979)

(untitled) - Kowalczyk, Z.; Jodzis, S.; Raróg, W.; Zieliński, J.; Pielaszek, J.; Presz, A. (Appl. Catal., A, 1999)

(untitled) - Kowalczyk, Z.; Krukowski, M.; Raróg-Pilecka, W.; Szmigiel, D.; Zielinski, J. (Appl. Catal., A, 2003)

(untitled) - Hansen, T. W.; Hansen, P. L.; Dahl, S.; Jacobsen, C. J. H. (Catal. Lett., 2002)

(untitled) - Raróg-Pilecka, W.; Miśkiewicz, E.; Kępiński, L.; Kaszkur, Z.; Kielar, K.; Kowalczyk, Z. (J. Catal., 2007)

(untitled) - Yang, Z.; Guo, W.; Lin, J.; Liao, D. (Chin. J. Catal., 2006)

(untitled) - Vidick, D.; Leonard, A. F.; Poleunis, C.; Delcorte, A.; Devillers, M.; Hermans, S. (Catal. Today, 2014)

(untitled) - Mingos, D. M. P.; Watson, M. J. (Adv. Inorg. Chem., 1992)

(untitled) - Willocq, C.; Vidick, D.; Tinant, B.; Delcorte, A.; Bertrand, P.; Devillers, M.; Hermans, S. (Eur. J. Inorg. Chem., 2011)

(untitled) - Moggi, P.; Albanesi, G.; Predieri, G.; Spoto, G. (Appl. Catal., A, 1995)

(untitled) - Aika, K.-i.; Takano, T.; Murata, S. (J. Catal., 1992)

(untitled) - Guo, S.; Pan, X.; Gao, H.; Yang, Z.; Zhao, J.; Bao, X. (Chem. – Eur. J., 2010)

(untitled) - Li, Z. L.; Liang, C. H.; Feng, Z. C.; Feng, Z. C.; Ying, P. L.; Wang, D. Z.; Li, C. (J. Mol. Catal. A: Chem., 2004)

(untitled) - Raróg-Pilecka, W.; Miśkiewicz, E.; Szmigiel, D.; Kowalczyk, Z. (J. Catal., 2005)

(untitled) - Liang, C.; Li, Z.; Qiu, J.; Li, C. (J. Catal., 2002)